Rare Pancreatic Tumors - Choudhari, Amitkumar; Kembhavi, Pooja; Ramadwar, Mukta; Katdare, Aparna; Smriti, Vasundhara; Baheti, Akshay D. (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Pancreatic ductal adenocarcinoma, neuroendocrine tumor, and cystic pancreatic neoplasms are the common pancreatic tumors most radiologists are familiar with. In this article we review the clinical presentation, pathophysiology, and radiology of rare pancreatic neoplasms. While the imaging features are usually nonspecific and diagnosis is based on pathology, the radiology along with patient demographics, history, and laboratory parameters can often help indicate the diagnosis of an uncommon pancreatic neoplasm and guide appropriate management in these cases.
Keywords: pancreatic cancer; uncommon; pancreatoblastoma; acinar cell; lymphoma